Molecular characterization of Listeria monocytogenes in bovine milk and evaluating the sensitivity of PCR for direct detection in milk - LAXIMAN, SAWANT; KAUR, SIMRANPREET; AULAKH, R S; GILL, J P S (The Indian Journal of Animal Sciences, 2016)
Food-borne listeriosis, recognized as an emerging bacterial disease of humans and animals worldwide, is caused by L. monocytogenes with at least 95% of the strains isolated from foods and patients belonging to serovars 1/2a, 1/ 2b and 4b. Milk and dairy products were implicated as sources of listeriae in several widely publicized incidents, thus suggesting that the mammary glands of mastitic cattle may be an important reservoir of Listeria. In the present study, 350 bovine milk samples were collected for prevalence and molecular characterization studies of Listeria spp. The isolates were phenotypically and genotypically characterized by biochemical tests, haemolysis on sheep blood agar, CAMP test, PI-PLC assay and multiplex PCR targeting virulence cluster genes namely haemolysin (hlyA), PI-PLC (plcA), actin (actA), p60 (iap) and regulatory (prfA); along with multiplex PCR for typing major serovars targeting lmo0737, ORF2819, ORF2110 and prs genes. Four pathogenic L. monocytogenes were recovered indicating prevalence rate of 1.14% in milk while the overall prevalence rate of Listeria spp. was 1.42%. All the four pathogenic isolates were characterized as L. monocytogenes serotype 4b. Antibiogram of the pathogenic L. monocytogenes isolates revealed sensitivity for amikacin, gentamycin, norfloxacin and doxycyclin. Animal sera (169) screened by indirect ELISA for antibodies against listeriolysin O showed sero-positivity of 7.1%. Sensitivity of PCR for direct detection from milk was evaluated to be 8.8 × 105 L. monocytogenes cells/ml of milk. Thus, the presence of pathogenic strains of L. monocytogenes in raw milk appeared to be a cause for concern with profound public health implications.